2018
DOI: 10.3390/polym10101176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extractives on Dimensional Stability, Dynamic Mechanical Properties, Creep, and Stress Relaxation of Rice Straw/High-Density Polyethylene Composites

Abstract: The removal of rice straw extractives increases the interphase adhesion between rice straw and the high-density polyethylene (HDPE) matrix, while eradicating the inner defects of rice straw/HDPE composites. This study investigated the effect of rice straw extractives removal on the dimensional stability (water uptake and thermal expansion), dynamic mechanical properties, creep, and stress relaxation of rice straw/HDPE composites. Cold water (CW), hot water (HW), and 1% alkaline solution (AL) extraction methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The homogeneously dispersed CW‐RS, HW‐RS, and AL‐RS in the extracted RS/HDPE composites (Figure 6) proved that the extracted RS fibers were between coated well by the HDPE matrix. The dimensional stability, dynamic mechanical properties, creep, and stress relaxation investigated by our group confirmed that the inner bonding of RS/HDPE was poor and the removal of the extractives of RS improved the combination between the RS and the HDPE matrix and enhanced the inner bonding of the composites 45 …”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The homogeneously dispersed CW‐RS, HW‐RS, and AL‐RS in the extracted RS/HDPE composites (Figure 6) proved that the extracted RS fibers were between coated well by the HDPE matrix. The dimensional stability, dynamic mechanical properties, creep, and stress relaxation investigated by our group confirmed that the inner bonding of RS/HDPE was poor and the removal of the extractives of RS improved the combination between the RS and the HDPE matrix and enhanced the inner bonding of the composites 45 …”
Section: Resultsmentioning
confidence: 60%
“…The dimensional stability, dynamic mechanical properties, creep, and stress relaxation investigated by our group confirmed that the inner bonding of RS/HDPE was poor and the removal of the extractives of RS improved the combination between the RS and the HDPE matrix and enhanced the inner bonding of the composites. 45 Die swell is a common phenomenon in HDPE composites extrusion and there was evident die swell in the RS/HDPE composites during processing (Figure 7). 24,25 The thickness of the RS/HDPE expanded 35.75%.…”
Section: The Internal State Of Rs/hdpe Compositesmentioning
confidence: 99%
“…Therefore, the literature shows how different types of fillers have been incorporated into HDPE to produce low cost HDPE composites, obtaining materials with improved mechanical properties and less environmental impact [ 22 , 23 , 24 ]. Most of these composites use mineral fillers [ 25 ] or fillers from agricultural waste [ 26 , 27 ]. Unlike agroforestry waste fillers, fillers from leather industry waste are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have used RS in the form of short fiber or particulate. 8,15,[21][22][23][24][25][26] The aim of this study is to form RS in a sheet in which the RS was bonded with each other uniformly. These sheets of RS fibers help to fabricate RS/polyester composites with any complex geometry.…”
Section: Introductionmentioning
confidence: 99%